Women's Media: History of its Emergence and Development, its Place in Kurdish Media "A Historical Analytical Study" - Khadr, Dr. Shilan Yasin (Sulaimani Journal for Humanities, 2026)
Media, like any other field, has become scientifically open and specialized, such as: (political, economic, social, financial, women, scientific, literary, artistic, sports, ...). The summary of this study is to feel the problems, which is to discuss the beginning of the emergence of women's media and highlight the content of the publications that were published on women. Its importance is to highlight the historical aspects of private media, especially women's media. One of the objectives of this study is to identify the services provided by women's media. This study is a historical analytical study with its own characteristics. Finally, the researchers make several suggestions, including: Organizations and relevant parties to pay more attention to this field and go deeper into this field and try to establish a television channel dedicated to women in Kurdistan. The most important recommendation is to support women's media and try to promote them.
Keywords: Specialized media; womens media